Neostigmine for non-mild acute pancreatitis: A systematic review and meta-analysis of randomized controlled trials - He, Kun; Wang, Yabing; Li, Jianing; Bai, Xiaoyin; Yang, Zihan; Han, Xianlin; Wu, Dong (Frontiers in Pharmacology, 2023)
Background: The therapeutic value of neostigmine as a prokinetic drug in acute pancreatitis (AP), especially in non-mild AP, including moderately severe and severe AP remains controversial. This meta-analysis aimed to investigate the efficacy of neostigmine treatment in patients with non-mild AP. Methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang databases up to 24 December 2022 for RCTs comparing neostigmine plus conventional treatment versus the conventional treatment alone in patients with non-mild AP. Trial sequential analyses (TSA) were used to assess the risk of random errors and the results. Results: Six RCTs with 318 participants were included. Compared with conventional treatment, patients who received neostigmine plus conventional treatment had a shorter time duration for their first defecation (MD: −1.74; 95% CI: −2.10 to −1.38; p < 0.00001; n = 205; RCTs = 4; low quality of evidence) and better relief time of abdominal symptoms (MD: −1.59, 95% CI: −2.07 to −1.11; p < 0.00001; n = 155; RCTs = 3; low quality of evidence) as primary outcomes, and a faster percentage decrease of IAP at 24 h (p = 0.0005; moderate quality of evidence) and a shorter length of ICU stay (p < 0.00001; moderate quality of evidence) as partial secondary outcomes. TSA suggested the sample size was limited, but the cumulative Z curves of the primary outcomes crossed the conventional boundary and the trial sequential monitoring boundary. Conclusion: For patients with non-mild AP, neostigmine promotes the recovery of gastrointestinal motility and may have positive effects on the improvement of a clinical prognosis. Further large-sample studies are needed for a definite conclusion. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/; Identifier: CRD 42022381417.